2021
DOI: 10.3390/catal11121545
|View full text |Cite
|
Sign up to set email alerts
|

Vinylogous and Arylogous Stereoselective Base-Promoted Phase-Transfer Catalysis

Abstract: Vinylogous enolate and enolate-type carbanions, generated by deprotonation of α,β-unsaturated compounds and characterized by delocalization of the negative charge over two or more carbon atoms, are extensively used in organic synthesis, enabling functionalization and C–C bond formation at remote positions. Similarly, reactions with electrophiles at benzylic and heterobenzylic position are performed through generation of arylogous and heteroarylogous enolate-type nucleophiles. Although widely exploited in metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 151 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…Thanks to this, phasetransfer catalysis proved to be suitable for many arylogous CÀ C bond formation where homogeneous organocatalysis has failed. [10] In this respect, we recently reported the highly diastereoselective arylogous Michael addition of γ-aryl phthalides catalyzed by alkali bases and crown ethers. [8] The extension of this methodology to γ-unsubstituted phthalides was achieved by adding stoichiometric amounts of the silylating agent N,O-bis(trimethylsilyl)acetamide (BSA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to this, phasetransfer catalysis proved to be suitable for many arylogous CÀ C bond formation where homogeneous organocatalysis has failed. [10] In this respect, we recently reported the highly diastereoselective arylogous Michael addition of γ-aryl phthalides catalyzed by alkali bases and crown ethers. [8] The extension of this methodology to γ-unsubstituted phthalides was achieved by adding stoichiometric amounts of the silylating agent N,O-bis(trimethylsilyl)acetamide (BSA).…”
Section: Introductionmentioning
confidence: 99%
“…This latter feature allows the activation of extremely weakly acidic pronucleophiles, despite the non‐anhydrous conditions employed. Thanks to this, phase‐transfer catalysis proved to be suitable for many arylogous C−C bond formation where homogeneous organocatalysis has failed [10] . In this respect, we recently reported the highly diastereoselective arylogous Michael addition of γ‐aryl phthalides catalyzed by alkali bases and crown ethers [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In the variegated panorama of natural products, the chiral phthalide framework is a recurrent structural motif that is frequently associated with relevant and diverse biological activities and therefore object of continuous effort in developing stereoselective synthetic methodologies. , On our side, given the large availability of simple phthalide building blocks, we have pursued over the past few years a strategy for building more complex structures based on the stereocontrolled formation of a C–C bond at the γ-site of the lactone ring. , …”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49][50] Functionalized anthrone derivatives can be synthesised by non-asymmetric and asymmetric 1,4-addition, as well as Diels-Alder reactions. [51][52][53][54] While Kitamura et al reported the coupling of 2-hydroxyindoline with anthrone using BF 3 -$Et 2 O, 55 and White's group established a two-step technique employing Fe(PDP)-catalyzed oxidation followed by 1,2-addition of anthrone, 56 the 1,2-addition of imine remains undiscovered. Recently, researchers reported for the rst time a Et 3 N direct 1,2-addition of anthrone to N-sulfonylaldimines over moderate conditions, resulting in benzyl amine functionalized anthrone.…”
Section: Introductionmentioning
confidence: 99%